Detection of Surra (trypanosomiasis) positivity in humans in an outbreak area of Indonesia (Medical Journal of Indonesia, 2019)
BACKGROUND Surra is an infection caused by a blood protozoan parasite, Trypanosoma evansi, and transmitted by blood-sucking insects. The parasite generally infects only animals; however, it was reported to infect an Indian cattle farmer in 2004, followed by reports of other human cases. The most severe Surra outbreak in Indonesia occurred in Sumba Island during 2010-2012, resulting in the death of more than 2,000 livestock. This study was conducted to explore the serological status of farmers who have intensive contact with their livestock against T. evansi infection in Southwest Sumba district. METHODS A total of 24 serum samples were collected from farmers living in the Surra outbreak area. All sera were tested using both card agglutination test for trypanosomiasis/T. evansi (CATT/T. evansi) and field enzyme-linked immunosorbent assay (FELISA). RESULTS Of the 24 serum samples, 4 (16.7%) samples were seropositive for the antigen T. evansi using both tests. This is the first report of human trypanosomiasis (Surra) in Indonesia. Unfortunately, the clinical manifestations of farmers with positive Surra infection were not reported because all sera samples used in this study were obtained from the Public Health Service with no reports of clinical signs from the respondents. CONCLUSIONS Farmers living in the Surra outbreak area have a high risk of being infected with T. evansi due to their potential frequent contact with Surra vectors. Therefore, T. evansi infection in humans requires attention as it might have the potential to develop as a new emerging zoonotic disease in Indonesia.